2009
DOI: 10.1590/s1677-55382009000300012
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the anti-neoplastic activity of curcumin in prostate cancer cell lines

Abstract: Objective: The aim of our study is to investigate the anti-neoplastic effect of curcumin in prostate cancer cell lines. Specifically, we are using the LNCaP cell line and another prostate cell line developed in our laboratory, PcBra1. The PcBra1 cells were derived from a localized, obstructive prostate cancer with a Gleason score of 9 (4+5). Materials and Methods: A prostate cancer cell line was isolated from a localized, obstructive prostate cancer with a Gleason score of 9 (4+5), and it was characterized usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 23 publications
0
17
0
3
Order By: Relevance
“…Even when 10-12 g/ml of curcumin was administered orally in humans, curcumin levels in serum remained approximately at 50 ng/ml [24]. Several studies demonstrated that 10-50 μM (3.7-18.4 μg/ml) curcumin induces cell death primarily through apoptosis [25,26]. However, the important question to be addressed is how to bring curcumin at these micromolar concentrations to the site of tumors while curcumin possesses such a low bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Even when 10-12 g/ml of curcumin was administered orally in humans, curcumin levels in serum remained approximately at 50 ng/ml [24]. Several studies demonstrated that 10-50 μM (3.7-18.4 μg/ml) curcumin induces cell death primarily through apoptosis [25,26]. However, the important question to be addressed is how to bring curcumin at these micromolar concentrations to the site of tumors while curcumin possesses such a low bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin lacks toxicity in humans (1), and extensive research over several decades has revealed that curcumin possesses anticancer, anti-inflammatory, antioxidant, antiviral and anti-bacterial activities (2,3). Curcumin suppressed cell proliferation or induced apoptosis in cultured prostate cancer cells and other types of cancer cells (4)(5)(6)(7)(8)(9)(10). Curcumin also inhibited prostate carcinogenesis (11).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the anticancer activity of curcumin and curcumin analogues in animal models [2][3][4][5][6][7] as well as growth inhibition and apoptosis induction in a variety of cancer cell lines in vitro. [8][9][10][11][12][13][14][15][16] However, the clinical efficacy of curcumin is limited, which is likely due to its low bioavailability. [17][18][19] We have previously reported on the synthesis and evaluation of sixty-one curcumin-related compounds for inhibitory effects on cultured prostate cancer cells, pancreatic cancer cells and colon cancer cells.…”
mentioning
confidence: 99%